No Gastrointestinal Dysmotility in Transgenic Mouse Models of Migraine. Issue 2 (26th December 2019) - Sprouse Blum, Adam S.; Lavoie, Brigitte; Haag, Melody; Mawe, Seamus M.; Tolner, Else A.; van den Maagdenberg, Arn M.J.M.; Chen, Shih‐Pin; Eikermann‐Haerter, Katharina; Ptáček, Louis; Mawe, Gary M.; Shapiro, Robert E.
Abstract : Objective: To determine whether transgenic mouse models of migraine exhibit upper gastrointestinal dysmotility comparable to those observed in migraine patients. Background: There is considerable evidence supporting the comorbidity of gastrointestinal dysmotility and migraine. Gastrointestinal motility, however, has never been investigated in transgenic mouse models of migraine. Methods: Three transgenic mouse strains that express pathogenic gene mutations linked to monogenic migraine‐relevant phenotypes were studied: CADASIL ( Notch3 ‐Tg88), FASP ( CSNK1D ‐T44A), and FHM1 ( CACNA1A ‐S218L). Upper gastrointestinal motility was quantified by measuring gastric emptying and small intestinal transit in mutant and control animals. Gastrointestinal motility was measured at baseline and after pretreatment with 10 mg/kg nitroglycerin (NTG). Results: No significant differences were observed for gastric emptying or small intestinal transit at baseline for any of the 3 transgenic strains when compared to appropriate controls or after pretreatment with NTG when compared to vehicle. Conclusions: We detected no evidence of upper gastrointestinal dysmotility in mice that express mutations in genes linked to monogenic migraine‐relevant phenotypes. Future studies seeking to understand why humans with migraine experience delayed gastric emptying may benefit from pursuing other modifiers of gastrointestinal motility, such as epigenetic or microbiome‐related factors.